Implementation of industrial internet of things technologies using Edge, Fog, and Cloud computing - Gasimov, V.A.; Aliyeva, Sh.Kh.; Assanova, Zh.S. (Problems of Informatization and Management, 2023)
Having superior features of productivity of the Industrial Internet technology of things used in the establishment of clever cities and clever villages, optimity, etc. increases the need to use it. The low-capacity of the physical resources of Iot-based sensors allows it to integrate into cloud technology. Cloud-based infrastructures are not sufficient for the existing requirements of the products of the products. The two main issues, in terms of reconciliation and network expansion limits arise. Also, the breaks of the Internet connection, the low conductivity, etc., as such problems, allow IIOT to integrate the "Fog Computing" and "Edge Computing" technologies. Taking into account the coverage and development of IIOT technology, it is believed that in many cases taking advantage of its full potential will be possible to combine clouds, fog and edge calculations. In this article, Industrial Internet technology of things, its integrated "Cloud", Fog ", Edge technologies are being investigated and differences between them, distribution-based approaches between levels are discussed.